2001
DOI: 10.1007/pl00000264
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of mast cells in morphine-mediated impairment of zymosan-induced peritonitis in mice

Abstract: Mast cell-derived factors are involved in morphine-mediated impairment of zymosan-induced peritonitis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…In agreement with these studies, we observed that the PDF-induced cell influx was significantly reduced in Ws/Ws rats or in wild-type rats that were treated with cromoglycate. Along with a poor cell influx, Ws/Ws rats and rats that were treated with cromoglycate developed a weak milky spot response, which might explain the poor influx response that was found in mast cell-deficient rats in this study and during peritonitis (27,28). We therefore suggest a novel role for mast cells in the induction of a proper omental milky spot response, providing new opportunities to regulate peritoneal cell recruitment.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In agreement with these studies, we observed that the PDF-induced cell influx was significantly reduced in Ws/Ws rats or in wild-type rats that were treated with cromoglycate. Along with a poor cell influx, Ws/Ws rats and rats that were treated with cromoglycate developed a weak milky spot response, which might explain the poor influx response that was found in mast cell-deficient rats in this study and during peritonitis (27,28). We therefore suggest a novel role for mast cells in the induction of a proper omental milky spot response, providing new opportunities to regulate peritoneal cell recruitment.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, milky spots are the sites for local proliferation, maturation, and differentiation of macrophages (10). It has been reported that the inherited mast cell deficiency in experimental peritonitis models significantly impaired the cell influx (27,28); however, no explanation was provided. Jippo et al (29) elegantly showed that tissue mast cells, not those in the peritoneal fluid, are essential for a proper innate immunity against bacterial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 48/80 (1.2 mg/kg) was given daily for 4 days before the first challenge period as well as daily throughout the first challenge period for a total of 10 days (21,22). Sodium cromoglycate (cromolyn; SigmaAldrich; 400 mg/kg) was i.p.…”
Section: Induction Of Experimental Asthmamentioning
confidence: 99%
“…The zymosan-induced increase in peritoneal vasopermeability is accompanied by rapid efflux of histamine from peritoneal mast cells as shown by lack of its presence in mast cell-deficient or depleted mice [11,12]. The two processes are correlated in time and both reach their maximal values 30 min after induction of inflammation [11].…”
Section: Mediators Involved In the Early Increase Of Vascular Permeabmentioning
confidence: 99%
“…Moreover, some studies were conducted on Balb/c mice with the malfunctioning mast cells (blockage of degranulation by MC membrane-stabilizator) or histamine receptors (H 1 -and H 2 -receptor antagonists preventing histamine action) [11]. Alternatively, depletion of mast cells with compound 48/80 was used [1,12]. Either treatment led to significant, albeit slight, inhibition of early vascular permeability.…”
Section: Mediators Involved In the Early Increase Of Vascular Permeabmentioning
confidence: 99%